2021
DOI: 10.1371/journal.pone.0248625
|View full text |Cite
|
Sign up to set email alerts
|

Media and social media attention to retracted articles according to Altmetric

Abstract: The number of retracted articles has grown fast. However, the extent to which researchers and the public are made adequately aware of these retractions and how the media and social media respond to them remains unknown. Here, we aimed to evaluate the media and social media attention received by retracted articles and assess also the attention they receive post-retraction versus pre-retraction. We downloaded all records of retracted literature maintained by the Retraction Watch Database and originally published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…35 There has been evidence of social media spreading the misinformation in retracted articles making them so popular that its retraction is deemed insignificant at times. 6 36 37 A similar study done on post-retraction AAS shows that most retracted articles and their retraction notice receive media and social media attention. 6 In fact, retracted articles tend to receive more media and social media attention than very similar, matched unretracted articles.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…35 There has been evidence of social media spreading the misinformation in retracted articles making them so popular that its retraction is deemed insignificant at times. 6 36 37 A similar study done on post-retraction AAS shows that most retracted articles and their retraction notice receive media and social media attention. 6 In fact, retracted articles tend to receive more media and social media attention than very similar, matched unretracted articles.…”
Section: Discussionmentioning
confidence: 73%
“… 6 36 37 A similar study done on post-retraction AAS shows that most retracted articles and their retraction notice receive media and social media attention. 6 In fact, retracted articles tend to receive more media and social media attention than very similar, matched unretracted articles. The cause of this misinformation popularity, without any mention of its retraction, can be partly blamed on journals.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Notable recent examples include a RCT of ivermectin [7] and a cohort study of hydroxychloroquine, both for COVID-19 [8]. An increasing number of studies have investigated the fate of such retracted studies: some studies have evaluated the impact of retracted articles on social media [9] or reported on the ongoing citations of retracted articles in some specialties such as radiation oncology, dentistry or COVID-19 [6,1012]. The Cochrane has developed a new policy to address potentially problematic studies including retraction [4].…”
Section: Introductionmentioning
confidence: 99%